Comparative Analysis of Educational Policies and Systems: A Case Study of Egyptian and Indonesian Higher Educations - Kusumajati, Cahya (Jurnal Pendidikan Islam, 2024)
Egypt and Indonesia are two countries with the development of Islamic civilization in the region, apart from that they are also synonymous with the lives of their religious communities. The existence of an advanced civilization is caused by good education. With education, society and civilization will develop. One of the signs that Egypt has become a center of civilization is because of the many scientific councils and universities that have developed there, such as Al-Azhar University. Meanwhile, Indonesia shows that there are many Islamic universities scattered around. The aim of this research is to analyze the comparison of higher educational policies and systems in Egypt and Indonesia which are implemented in this modern era. The method used is qualitative research, sample selection through snowball sampling, data collection through interviews, and data validity testing through data triangulation. The results of the research show that the educational policy at Al-Azhar University includes a mandatory Al-Qur'an memorization program for all students, as well as mandatory programs at Universitas Islam Indonesia (UII) or the Indonesian Islamic University, namely pesantren and taklim. The educational system at Al-Azhar University uses a method that focuses on lecturers, there are no class attendance lists, so students are free to study inside or outside the classroom. Meanwhile, at UII, learning focuses on lecturers and students so that class attendance is mandatory. This article contributes to comparing the educational policies and systems of Al-Azhar University and Universitas Islam Indonesia, and provides insights to improve the quality of education in Islamic universities.